CHANGING OF DAIRY PRODUCTIVITY LEVEL AND PHYSICAL AND CHEMICAL PROPERTIES OF MILK FROM COWS WITH DIFFERENT TYPES OF FEEDING - Razhamuradov, Z.T. (International Journal of Psychosocial Rehabilitation, 2020)
Scientific and economic and physiological experiments to study the influence of silage and hay feeding type in lactating cows of the German generation were carried out in the conditions of the Pastdargom district of the Samarkand region. For this purpose two groups ofcowsin the third lactation of Holstein breed were formed with 6 head of catlle in each group. The animals of the control group received a silаge diet, and the cows of the experimental group received the haylage type ofdiet, and in the diets of the compared groups, the nutrient content was almost the same and corresponded to the feeding standards of A.P. Kalashnikov et al. (2003). It was found that when using a haylage-type of diet cows consumed, more nutrients by 2.1% compared with the control group. In this way, the average daily milk yield in cows of experimental groups was greater at 3, 40 kilograms or 23.49 ± 0.37 kg versus 20.09 ± 0.51 kg. In the experimental group, there was an increase in the mass fraction of protein by 5.4 and fat by 10.5% relative to the control group oh. The dry skim milk remnantsin the milk of experimental group made 8.44 %, which was largercompared to the control group at 0.51%. The lowest level of milk density was in the experimental group of 1027.9 kg / cm 4, while the highest fat content was compared to the control group (4.09). The results of studies showed that the use of haylage type of feeding in cows of the Holstein breed to a certain extent improved the state of digestion processes in the paunch and the qualitative properties of raw milk.